(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
This study investigated the effect of a complex biological supplement composed of chitosan sulfate and whey powder on hepatic microsomal enzymes and lipid peroxidation processes under metabolic syndrome conditions. The findings demonstrated that metabolic syndrome induction reduces NADPH–cytochrome C reductase and amidopyrine demethylase activity and increases lipid peroxidation 2.7-fold. Administration of the chitosan–whey complex restored enzyme activity by 89–93% and reduced MDA levels by 52%. The results scientifically justify the hepatoprotective potential of the bioactive complex and its possible application in veterinary and biomedical fields.